Tentorial vascularization in solid hemangioblastoma - Case report - Ozveren, MF; Topsakal, C; Erol, FS; Kaplan, M; Uchida, K; Tanik, C (Japan Neurosurgical Soc, 2001)
A 40-year-old female was admitted to the hospital with complaints of headache worsening gradually over a 1-month duration, Her past history included surgery to treat a left cerebellar cystic lesion 3 years before, and an untreated small solid right supracerebellar lesion of 1 cm diameter. On admission, magnetic resonance imaging showed that the right cerebellar lesion had grown to approximately 4 cm diameter abutting the tentorium and causing obstructive hydrocephalus. She also had two more small lesions, a right supratentorial solid lesion with cystic component near the splenium and an intramedullary cystic lesion at the C-2 level. Right suboccipital craniectomy was done, The vascular attachments between the superior aspect of the tumor and the tentorium were coagulated and the tumor was totally removed. C1-2 laminectomy was also performed to drain the intramedullary cyst. The patient deteriorated and lost consciousness with respiratory arrest 6 hours postoperatively and was reoperated for intracerebellar hematoma due to oozing from the tentorial vessels. Histological investigation revealed hemangioblastoma. Dural tentorial vascular attachments in solid hemangioblastomas located subjacent to the tentorium may cause early postoperative complications of hematoma at the site of vascular attachment following the resection, Computed tomography study in the early postoperative period is helpful to identify this problem.
Keywords: postoperative hemorrhage; solid hemangioblastoma; tentorial vascularization